PERUBAHAN SISTEM KONTROL DARI PLC KE DCS PADA GRUP BAG FILTER 563-BF1 - Jefri Gunawan; Fatahula Fatahula; Juhartono Juhartono (Politeknik Negeri Jakarta, 2019)
Bag filter is an equipment in cement industries that used for handling dust from material or separate fines dust with air to make the area is not dusty and it is not make accumulation material. Bag filter (563-BF1) is used for handling dusty area at outlet ball mill in the cement making process. The working systems of bag filter group (563-BF1) is controlled by PLC (Programmable Logic Control). However, the PLC is obsolete so it takes a long time to handle when damage occurs and causes the risk of production loss reach Rp 1,301,801,760.00. In addition, communication systems between PLC with Central Control Room (CCR) that are less reliable cause communication to fail on April 2019 so that the equipment cannot be controlled. To overcome this, it is necessary to upgrade the PLC and communication system to the latest version or change it to DCS (Distributed Control System). Upgrading PLC requires huge costs with almost the same communication system reliability. While changing the control system to DCS is cheaper with better reliable system. So, we chose to change it to DCS. After that control system is changed to DCS on April 2019, the risk of production loss can be eliminated with saving cost in the amount of Rp 220,402,885.00 and after 3 month the communication failed is never occurs (it is more reliable).